2015
DOI: 10.4103/0970-9371.155223
|View full text |Cite
|
Sign up to set email alerts
|

Clinical audit of ultrasound guided fine needle aspiration in a general cytopathology service

Abstract: Background:Studies on ultrasonography (USG) guided fine needle aspiration cytology (FNAC) have been conducted in specialized settings such as thyroid, breast, and intra-abdominal aspirates. There is a paucity of literature on the practices of guided FNAC in a general cytopathology service.Aim:The aim was to determine prevailing practices of USG guided FNAC in a general cytopathology service of a teaching hospital.Settings and Design:Metropolitan hospital, clinical audit.Materials and Methods:Audit of 112 USG g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 27 publications
1
5
0
1
Order By: Relevance
“…Mangla et al conducted an audit of USG guided FNaC over a period of one year in a general cytopathology service based in Delhi catering to a similar patient population as in the present study (20). They observed that only 112 USG guided FNaCs were performed out of a total of 7795 FNaC.…”
Section: Discussionmentioning
confidence: 99%
“…Mangla et al conducted an audit of USG guided FNaC over a period of one year in a general cytopathology service based in Delhi catering to a similar patient population as in the present study (20). They observed that only 112 USG guided FNaCs were performed out of a total of 7795 FNaC.…”
Section: Discussionmentioning
confidence: 99%
“…In a study of guided FNAC in mixed pediatric and adult population, majority cases were that of thyroid lesions while in our study, lymph nodes appear to be the commonest organ to be sampled in the pediatric population. 10 The commonly detected non-neoplastic lesions in our study were infective with equal number of tubercular and bacterial lesions. Rest all other lesions were in almost similar frequency.…”
Section: Discussionmentioning
confidence: 55%
“…Out of 30 cases, 16 were females and 14 males with majority of males in the age group of 0 to 10 years and majority females in the age group of 11 to 18 years. The most common site to undergo FNAC in our experience was abdominal swellings [mesenteric lymph nodes (10) followed by kidney mass (2) and ovarian mass (2)]. Only 3 cases were categorized as neoplastic, malignant lesions, the rest were non-neoplastic.…”
Section: Resultsmentioning
confidence: 95%
“…Клинический аудит широко используется не только в сферах лечения, но и при оценке правильности прове-дения различных диагностических процедур: например, при выполнении рентгенологических исследований [44,45], экспресс-тестов [46], аспирационных биопсий [47].…”
Section: терминологияunclassified